-6u+2(u+6)=-24

Simple and best practice solution for -6u+2(u+6)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u+2(u+6)=-24 equation:


Simplifying
-6u + 2(u + 6) = -24

Reorder the terms:
-6u + 2(6 + u) = -24
-6u + (6 * 2 + u * 2) = -24
-6u + (12 + 2u) = -24

Reorder the terms:
12 + -6u + 2u = -24

Combine like terms: -6u + 2u = -4u
12 + -4u = -24

Solving
12 + -4u = -24

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -4u = -24 + -12

Combine like terms: 12 + -12 = 0
0 + -4u = -24 + -12
-4u = -24 + -12

Combine like terms: -24 + -12 = -36
-4u = -36

Divide each side by '-4'.
u = 9

Simplifying
u = 9

See similar equations:

| 5x^2-37xy+14y^2=0 | | 3/4(4x-8) | | s^2+s=72 | | 4x+3(-2x+3)=-11 | | 3(x+4)=2(2x+5) | | 8x+8/3*6/32x+32 | | 6x-3(5x+6)=-99 | | -x^2+24x+180=f(x) | | 4x3+2x2-80x/2x | | -x^2+14x+180=f(x) | | 3(x+2)-7=3(x-1)+2 | | -8=-(2x+1)-3 | | 80+80= | | 6x-3(5x-9)=48 | | 3u+5=26 | | w+3w+8=2w+10 | | -36=-6+5x | | 6x+20=128 | | 5n^5+(-3n^5)= | | 6x-2y=34 | | 5x+15+2x+8=3 | | 5x+15+2x=3 | | -2x+5y=6 | | 0.05x-0.125x= | | y=(1/3x)+2 | | -7x-6(-2x+18)=-153 | | -5x+6y=7 | | 1/3x=1/2x+4 | | (3/2+p)*2^2=12 | | 12pm+4sm+21p+7s=0 | | 3x+6-x=10+x-9 | | -7x-6(-2x+14)=-24 |

Equations solver categories